Comment on Aminian et al. Cardiovascular Outcomes in Patients With Type 2 Diabetes and Obesity: Comparison of Gastric Bypass, Sleeve Gastrectomy, and Usual Care. Diabetes Care 2021;44:2552–2563 - Violante Cumpa, Jorge Rafael; Sánchez Gómez, Raymundo Abram; Lavalle González, Fernando Javier; Mancillas Adame, Leonardo Guadalupe (2022)
We read with great interest the article published by Aminian et al., where the authors found greater weight loss, better diabetes control, and lower risk of major adverse cardiovascular events 6 (MACE-6) (composite outcome including all-cause mortality, coronary artery events, cerebrovascular events, heart failure, atrial fibrillation, and nephropathy) for Roux-en-Y gastric bypass (RYGB) than for sleeve gastrectomy (SG) in patients with obesity and type 2 diabetes; however, we found some aspects of the study worth further discussion.